Diabetic Foot Infection: Causative Pathogens and Empiric Antibiotherapy Considerations—The Experience of a Tertiary Center. (June 2019) - Neves, José Miguel; Duarte, Bruno; Pinto, Margarida; Formiga, Ana; Neves, José
Most moderate-to-severe diabetic foot infections (DFIs) require hospitalization with urgent surgical approach and administration of empiric antibiotherapy. To ensure optimal antibiotic coverage, regular microbiological background updates are imperative. The purpose is to characterize the microbiological profile and the antibiotic sensitivity pattern of the DFI causative pathogens isolated within a specialized DFI unit of a tertiary hospital, in order to establish evidence-based policies regarding empirical antibiotic use. A cross-sectional study was conducted. Microbiological cultures and corresponding antibiotic sensitivity tests collected from moderate-to-severe DFIs as a first approach to the hospitalized patient were retrieved and analyzed during a 12-month period. Two groups were analyzed: inpatients that had been previously followed at the diabetic foot clinic of the hospital and inpatients without a previous contact with the hospital services. A total of 125 isolates obtained from 87 patients were deemed for analysis. Globally, a predominance of Gram-positive bacteria was observed (60%). Staphylococcus aureus was the most common pathogen. The global ratio of methicillin-sensitive S aureus to methicillin-resistant S aureus (MRSA) was 1.3:1, with similar findings in both groups. According to the antibiotic sensitivity test results, and within the recommended empiric antibiotic regimens for DFI, piperacillin/tazobactam seems to be the most suitable option. Gram-positive bacteria prevail as the main isolates in DFIs. Screening for MRSA-specific risk factors is mandatory. When going for a first empiric therapy, piperacillin/tazobactam is recommended in this institution, and an anti-MRSA agent should be added early, if necessary. We encourage continuous monitoring for the bacterial prevalence in Portuguese diabetic foot centers as it is paramount for the decision making regarding DFI protocols.